Lung Metabolic Activation as an Early Biomarker of Acute Respiratory Distress Syndrome and Local Gene Expression Heterogeneity. (November 2016) - Wellman, Tyler J.; de Prost, Nicolas; Tucci, Mauro; Winkler, Tilo; Baron, Rebecca M.; Filipczak, Piotr; Raby, Benjamin; Chu, Jen-hwa; Harris, R. Scott; Musch, Guido; dos Reis Falcao, Luiz F.; Capelozzi, Vera; et al.
Abstract : Background: Acute respiratory distress syndrome (ARDS) is an inflammatory condition comprising diffuse lung edema and alveolar damage. ARDS frequently results from regional injury mechanisms. However, it is unknown whether detectable inflammation precedes lung edema and opacification and whether topographically differential gene expression consistent with heterogeneous injury occurs in early ARDS. The authors aimed to determine the temporal relationship between pulmonary metabolic activation and density in a large animal model of early ARDS and to assess gene expression in differentially activated regions. Methods: The authors produced ARDS in sheep with intravenous lipopolysaccharide (10 ng ⋅ kg −1 ⋅ h −1 ) and mechanical ventilation for 20 h. Using positron emission tomography, the authors assessed regional cellular metabolic activation with 2-deoxy-2-[(18)F]fluoro-D-glucose, perfusion and ventilation with 13 NN-saline, and aeration using transmission scans. Species-specific microarray technology was used to assess regional gene expression. Results: Metabolic activation preceded detectable increases in lung density (as required for clinical diagnosis) and correlated with subsequent histologic injury, suggesting its predictive value for severity of disease progression. Local time courses of metabolic activation varied, with highly perfused and less aerated dependent lung regions activated earlier than nondependent regions. These regions of distinct metabolic trajectories demonstrated differential gene expression for known and potential novel candidates for ARDS pathogenesis. Conclusions: Heterogeneous lung metabolic activation precedes increases in lung density in the development of ARDS due to endotoxemia and mechanical ventilation. Local differential gene expression occurs in these early stages and reveals molecular pathways relevant to ARDS biology and of potential use as treatment targets. Abstract : Sheep pretreated with endotoxin were ventilated and studied with computed tomographic and positron emission tomographic scans followed by lung biopsy. Metabolic activation preceded radiographic infiltration and was colocalized with gene activation and histologic injury. This provides rationale for therapies directed at metabolic or gene products in adult respiratory distress syndrome.Supplemental Digital Content is available in the text.